Supply Chain Management Information System Model for Product Management for the Bank of Thailand - Artaphon Chansamut (ExcelingTech, 2022)
The paper aimed to develop supply chain management information system model for product management for the bank of Thailand and an evaluation of the model. A Samples are ten experts in the field of supply chain. The data is analysed by means and standardized deviations. The research result shows that the model consists of six elements namely main components, Supplier, Manufacture, distributors, retailers and Customer. the assessment of supply chain management information system model for product management for the bank of Thailand using Black-Box technique and the result of the assessment of supply chain management information system model for product management for the bank of Thailand is appropriate at the high level The model can support information system development.Â